Synthesis of iron based electrocatalyst for air-cathode mircrobial fuel cell (MFC) - Vignes, Rasiah (2015)
The world relies on major fossil fuels including oil and gas, which are predicted to deplete by 2042. At this critical stage, there is a dire need to look for alternative energy sources to reduce the dependency on fossil fuels. Rapid Industrialisation on the other hand has made the implementation of wastewater managements to be crucial even though it is energy intensive and money consuming. It has been known for the past decades that bacteria could be used to generate electricity from many substrates as in Microbial Fuel Cell (MFC). Thus, MFC could be a solution for environmental wastewater managements and at the same time would be able to solve the energy crisis by producing power. Platinum (Pt) for the past years has been widely used as the cathode catalyst to accelerate ORR and electron acceptance. Nevertheless, there is always been a driving force to produce a low-cost non precious metal catalyst for the cathode of a MFC. This work presents a preparation of non-precious iron-based electro catalyst responsible for ORR for air-cathode microbial fuel cell. Catalyst is synthesised by mixing Iron oxalate (recovered from industrial waste) and Phenanthroline in ethanol solution before being calcined under N2 atmosphere at 800⁰C for 2 hours. The cathode was fabricated by coating the catalyst. Performance of the iron-based catalyst was investigated in a single chamber air-cathode MFC where palm oil mill effluent (POME) was used as the anode substrate and anaerobic sludge as inoculums. The maximum Open Circuit Voltage recorded was 0.543 mV and the highest Power density drawn was 4.9 mW/m2 after 5 days. The physical properties of the catalyst were characterized via Brunauer Emmett Teller(BET), X-Ray Diffraction (XRD), Field Emmision Scanning Electron Microsopy (FESEM) analysis and the electrochemical properties was characterized by Cyclic Voltammetry (CV) analysis. This study shows that the synthesised catalyst is electrochemically active, and further surface modification should be done to increase its stability